2016
DOI: 10.1038/am.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

Nickel oxalate dihydrate nanorods attached to reduced graphene oxide sheets as a high-capacity anode for rechargeable lithium batteries

Abstract: In the search for high-capacity anode materials, a facile hydrothermal route has been developed to synthesize phase-pure NiC 2 O 4 ·2H 2 O nanorods, which were crystallized into the orthorhombic structure without using templates. To ensure the electrical conductivity of the nanorods, the produced NiC 2 O 4 ·2H 2 O nanorods were attached to reduced graphene oxide (rGO) sheets via self-assembly layer-by-layer processes that utilize the electrostatic adsorption that occurs in a poly(diallyldimethylammonium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…It is known that a broad range of TM-based compounds, such as TM oxides, chalcogenides, fluorides, phosphides, and nitrides, have been investigated as CTAMs, considerably broadening the choices of materials for high-performance LIBs [122][123][124][125][126][127][128][129][130]. Moreover, in comparison with graphite anodes, CTAMs definitely demonstrate adjustable reaction potentials according to the strength of the ionic bonds formed between the TM cations and anions [131].…”
Section: Conversion Reaction-based Materialsmentioning
confidence: 99%
“…It is known that a broad range of TM-based compounds, such as TM oxides, chalcogenides, fluorides, phosphides, and nitrides, have been investigated as CTAMs, considerably broadening the choices of materials for high-performance LIBs [122][123][124][125][126][127][128][129][130]. Moreover, in comparison with graphite anodes, CTAMs definitely demonstrate adjustable reaction potentials according to the strength of the ionic bonds formed between the TM cations and anions [131].…”
Section: Conversion Reaction-based Materialsmentioning
confidence: 99%
“…13 The conversion process in these electrodes is pivotal as it affects the initial Coulombic efficiencies, cycle retention, and reversibility of batteries. 4,5 Recently, it has been proposed from the literature 68 that additional capacity can arise from the electrode materials that undergo the conversion reaction, which brings more potential for utilizing conversion reaction-based electrode materials, giving strong potential for application for practical rechargeable batteries. Along with the conversion reaction, the agglomeration of electrode materials is another important factor because it is a frequent phenomenon among nanoparticles (NPs) when used as electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the NiC 2 O 4 ·2H 2 O nanowires had very poor initial capacities and very fast capacity decay as shown in Figure S7c , which reflects the fact that the large size of NiC 2 O 4 ·2H 2 O and poor contacts between NiC 2 O 4 ·2H 2 O and Ni ligaments are severely harmful to the electrochemical performances due to the poor electric conductivity of NiC 2 O 4 ·2H 2 O. 39 …”
Section: Resultsmentioning
confidence: 96%
“…Galvanostatic charges and discharges were performed within a voltage cutoff window of 3.0–0.005 V. Figure 10 b depicts the cyclic performances of NiC 2 O 4 ·2H 2 O@np-Ni electrodes (with ∼1.2 mg/cm 2 NiC 2 O 4 ·2H 2 O) against Ni commercial foam (Ni-CF) electrode with loading of NiC 2 O 4 ·2H 2 O (NiC 2 O 4 ·2H 2 O@Ni-CF, with ∼0.28 mg/cm 2 NiC 2 O 4 ·2H 2 O) at the current density of 100 mA/g. Amazingly, the NiC 2 O 4 ·2H 2 O@np-Ni exhibits a superb high specific capacity up to 3154 and 1910 mAh/g for the first discharge and charge, respectively, both of which are much higher than the reported values using oxalates anodes and the nanoporous metal-based SnO 2 /nanoporous Cu, MnO 2 /nanoporous Cu systems (see Tables S1 and S2 in the Supporting Information )., 39 44 The capacity loss in the first cycle is due to the formation of solid electrolyte interphase (SEI). After 30 cycles, the capacity still remains at 1247 and 1166 mAh/g for the discharge and charge, respectively.…”
Section: Resultsmentioning
confidence: 99%